Al-Islam dan Kemuhammadiyahan: How to Teach the Non-Muslim Students at Muhammadiyah Education University of Sorong - M Husnaini; Ahmad Syauqi Fuady; Irnie Victorynie (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2021)
The purpose of this study seeks to understand the model of Al-Islam and Kemuhammadiyahan (AIK) learning for non-Muslim students at Unimuda Sorong. The things researched about the implementation of AIK teaching, the obstacles faced by AIK lecturers in learning AIK for non-Muslim students, and the efforts to overcome the obstacles to AIK learning for non-Muslim students Unimuda Sorong. It is a qualitative research method. The study employed the snowball sampling method. The chosen participant was three lecturers who had experienced teaching Al-Islam and Kemuhammadiyahan. In specific, participants are lecturers from the Muhammadiyah Education University (Unimuda) of Sorong, Indonesia. This study's primary data source was obtained through semi-structured interviews emphasizing the participants' experiences. Thematic analysis was employed to analyze data. The results of this study AIK learning at Unimuda Sorong are carried out with a multicultural spirit, AIK learning at Unimuda is carried out in various ways. The obstacles during AIK learning include the availability of AIK learning resources literature, limited internet network access, and non-Muslim students' difficulties understanding Islamic religious terms in Arabic. Efforts were made to overcome these obstacles, namely teaching AIK as knowledge, not doctrine, communication between non-Muslim students and lecturers, and other Muslim students. Suggestions for further research are to make non-Muslim students the primary informants in the research.